The cost of national unity: the impact of memory on American history - Knepper, Brendan Andrew (Kansas State University, 2015)
The power of historical memory is readily apparent in the United States of America. Ask any descendent of veterans that served in war, and a plethora of reasons behind their willingness to fight will follow. As with any conflict, the enduring legacies of the war‘s aftermath are not always clear until years after the fact. Memory of the American Civil War took several different routes before finally settling on the "spirit of reconciliation" that came to dominate American society in the post-war era. In the South, the "Lost Cause" began to take hold with former Confederates attempting to justify their defeat and change the historical record to excuse their actions. As the winner in the war, the North did not need to come up with justification as to why they fought—they had secured the Union and destroyed the divisive institution, slavery. Gradually over time, Northerners and Southerners celebrated their veterans while simultaneously promoting reconciliation between the two sections. As a result, any emancipationist legacy from the end of the Civil War was relegated to irrelevancy in American society as Jim Crow settled in within the South for the next hundred years. Memory of the American Civil War continues to have lasting impact upon modern American society, especially with the sesquicentennial celebrations of the war‘s major battles. Lesser known, and yet equally as important, is the memory of the American Revolution. As with the "Lost Cause", the American Revolution experienced its own reconstruction with equal parts forgetting and remembering. Emerging from this "reconstruction" was what became known as the American identity. Thirteen disparate colonies became a solid monolith of Americanism in the reconstructed views of the Revolution, instead of the divided thirteen colonies they truly were. This thesis argues that the "Lost Cause" and spirit of reconciliation that permeated the post-war United States after the Civil War followed a tradition of desiring unity above all else at the expense of minority groups such as African Americans and Native Americans, that began with the American Revolution.
Keywords: History; American history; American History (0337); History (0578)